Análise de redes sociais através de softwares de ars e de data mining: um estudo de caso em turmas de graduação - Azevedo, Tatiana Barbosa de (2011)
This study reports the main methodological concepts of social network analysis tools and data mining. Based upon these concepts, we designed a study of informal social networks, formed by students from different institutions and different undergraduate courses. To develop this, work was done to identify the group to be analyzed, to define the problem, to develop and implement a qualitative questionnaire on social networks. Based on this survey was the mapping of networks, using software social network analysis (SNA), which identified the main actors in each network. Subsequently, we created a database with the key attributes of the individuals collected from different networks. On this basis data mining techniques for descriptive and predictive analysis of the attributes of power connectors were applied in order to identify the profile of the main actors of the networks. These results demonstrate the relationship between patient characteristics and form of participation in social networks